Cromo e zinco influenciam o restabelecimento de plantas de pepino enxertadas? - Bernardi, Lucas Giovani Pastore (Universidade Federal de São Carlos, 2019)
The essential and nonessential heavy metals zinc (Zn) and chromium (Cr), respectively, are found in natural or cultivated areas as contaminants and can cause direct damage to vegetative propagation. A plant species Cucumis sativus L. (cucumber) is cultivated using the grafting technique and, provides the crop with characteristics such as heavy metal stress tolerance. In addition, this species shows that it is widely investigated in scientific reports on physiological effects caused by clinical factors, or that it qualifies as a 'plant-model' in investigative studies. We examined the hypothesis that heavy metals influence the grafting reestablishment in cucumber plants grown in the nutrient solution. From this hypothesis, our objective was to evaluate the reestablishing of the post-grafting plant from the essential and non-essential root availability of heavy metals via nutrient solution. We collected, weekly, data of linear plant growth dimensions and quantified chlorophyll and carotenoids. The controls adopted were used from different availability of Zn and Cr heavy metals in isolation and in combination, and control treatment of heavy metals. We conducted a initial test for methodological adjustments and understanding of plant responses and, subsequently, the main experiments with robust data collection, such as plant growth measurements, gas exchange and enzymatic analyzes that are used in the current scientific paper model. To the initial teste, we performed an analysis of variance (ANOVA) to verify the relationships among the factors studied and the responses. As the ANOVA assumptions were cut from the ShapiroWilk (normality) and Levene (homogeneity of variance) tests. Then, the data means were compared, for example, from the Tukey test. All tests were conducted considering the significance level of α=0.05. Our study can conclude that the grafted cucumber plants showed no post-grafting plant reestablishment even after the application of heavy metals. The plants differed in vegetative growth according to the applied metal concentrations and the control treatment, however this pattern was not observed in relation to chlorophylls and carotenoids, which may be an indicator of full post-grafting plant reestablishment. Thus, we accept the scientific hypothesis by conclude that the essential heavy metal, zinc, and the nonessential, chromium, influence the reestablishment of the graft. In general, we conclude that heavy metals influenced post-grafting plant growth, however the grafting technique can promote a better antioxidant defense system evidenced by the non-alteration of photosynthetic pigments. However, the application of Cr and high doses of Zn affected the plant growth and increased the enzymatic activity of the plants submitted to these treatments.
Can heavy metals (chromium and zinc) influence the reestablishing of post-grafting plants?
Keywords: Enxertia; Metais pesados; Pepino; Propagação vegetativa; Grafting; Heavy metals; Cucumber; Plant propagation; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL